1992
DOI: 10.1128/aac.36.11.2462
|View full text |Cite
|
Sign up to set email alerts
|

Modification of cefixime bioavailability by nifedipine in humans: involvement of the dipeptide carrier system

Abstract: We studied the action of nifedipine on the bioavailablity of cefixime, a molecule absorbed via the gut wall dipeptide carrier system in the rat, and on the bioavailability of D-xylose, which is absorbed via a pH (and Na+-)-dependent transporter. Each compound was administered alone or in combination with 20 mg of nifedipine to eight healthy male volunteers. Nifedipine significantly increased the absorption rate of cefixime (20.7 + 4.3 versus 16 ± 3.5 mg/h in the absence of nifedipine). The absolute bioavailabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 13 publications
2
20
1
Order By: Relevance
“…The interesting clinical observation that the coadministration of cefixime with Ca 2ϩ channel blockers can increase the (14) suggested that there are mechanisms that can increase the level of cefixime uptake by PEPT1. It has been shown that this increase in transport by nifedipine also applies to the PEPT1 substrates cephalexin and amoxicillin (4,5,45), zwitterionic compounds that already show high intestinal absorption rates in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The interesting clinical observation that the coadministration of cefixime with Ca 2ϩ channel blockers can increase the (14) suggested that there are mechanisms that can increase the level of cefixime uptake by PEPT1. It has been shown that this increase in transport by nifedipine also applies to the PEPT1 substrates cephalexin and amoxicillin (4,5,45), zwitterionic compounds that already show high intestinal absorption rates in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…It is highly b-lactamase stable and, as a result, many organisms resistant to penicillin and some cephalosporins are susceptible to cefixime. As a third generation cephalosporin is more resistant to hydrolysis by the b-lactamases produced by gram-negative bacteria than first-generation cephalosporins, it is characterized by the presence of two nonesterified carboxylic functions and by its stability to acid hydrolysis, which is due to the presence of a vinyl group on the cephen nucleus [1][2][3]. The structural formula for cefixime is shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…However, the Ͼ2-log 10 decrease in Enterobacteriaceae counts during cefixime treatment in our study demonstrated that the antibiotic was present in the digestive tract of our rats. According to the pharmacokinetic study of cefixime in rats, the bioavailability of cefixime was estimated at 30% (data not shown) and comparable to the rat and human data previously described (18,39), so the part excreted in the gastrointestinal tract may be considered approximately 70%. Based on these observations, we hypothesized that cefixime was hydrolyzed during transit by the ␤-lactamases-producing strains of anaerobic endogenous flora as previously described (11,26,42).…”
Section: Discussionmentioning
confidence: 87%